Play therapy: an overview and marketing plan - McNeil Sallman, Cyndi (Kansas State University, 2007)
Play is essential to child development because it contributes to the cognitive, physical, social, and emotional well-being of children and youth. The integration of play and play therapy techniques with child and family therapy offers a creative, age appropriate way to provide mental health treatment. This report offers an overview of play therapy, the therapeutic value of play, the historical background, theory, techniques, materials, and settings. Further, it provides the reader with many therapeutic modalities in which to implement play in family therapy. Because play therapy is a specialized field, this report also provides the reader with information on how to use this to create a marketing niche. This report was written with the Masters’ or Doctoral student in mind, as well as practicing therapists; with hopes to provide them a creative avenue in which to enhance their current therapeutic modalities.
Keywords: play therapy; marketing play therapy practice; history of play therapy; types of play therapy; overview of play therapy; materials used in play therapy; Psychology, Clinical (0622); Psychology, Developmental (0620); Psychology, General (0621)